A Systematic Review on the Synthesis and Mechanisms of Silver and Copper Nanoparticles against Staphylococcus aureus - Maranan, Sally Mae Samson; Borja, Astrid Joy Belardo; Mendez, Eryka Mehri Mendoza; Cruz, Hanna Mariella Resurreccion; Sadural, Daniella Inocentes; Melana, Licca Casingal; Cruz, Jim Radam (Asian Journal of Biological and Life Sciences)
Antibiotic resistance among pathogenic bacteria impaired the purpose of antibiotics as different clinical conditions like Staphylococcal infections become more prevalent. With this, researchers studied different alternatives to address antibiotic resistance, including natural product research and nanomaterials. Like antibiotics, nanoparticles have shown excellent antibacterial properties against the physicochemical properties of bacteria to stop them from causing diseases. This study aims to evaluate the efficacy of silver nanoparticles (AgNPs) and copper nanoparticles (CuNPs) as antibacterial agents against S. aureus, a gram-positive bacteria, through a systematic review. Out of 4,382 studies obtained from PubMed and ScienceDirect, only 10 studies that passed the criteria were included. In this review, studies that were included discuss the characterization of nanoparticles and how each parameter affects them using TEM/SEM-EDX, DLS, XRD, UV-Vis, and zeta potential. Moreover, the studies that were gathered used a wet chemical method with sodium borohydride as the most common reducing agent to synthesize and stabilize the said nanoparticles. Results showed that both AgNPs and CuNPs presented increased zones of inhibition depending on their concentration. In contrast, AgNPs are better inhibitors of bacterial growth as compared to CuNPs; however, it should be noted that CuNPs are more effective for gram-positive bacteria, specifically S. aureus. Hence, both silver and copper nanoparticles could be considered good alternatives for antibiotics to fight against antibiotic-resistant bacteria.
Keywords: Antibacterial property; Copper nanoparticles; Silver nanoparticles; Staphylococcus Aureus; Wet chemical method